In vitro circadian rhythms: imaging and electrophysiology - Beaulé, Christian (2011)
In vitro assays have localized circadian pacemakers to individual cells, revealed genetic determinants of rhythm generation, identified molecular players in cell-cell synchronization and determined physiological events regulated by circadian clocks. Although they allow strict control of experimental conditions and reduce the number of variables compared with in vivo studies, they also lack many of the conditions in which cellular circadian oscillators normally function. The present review highlights methods to study circadian timing in cultured mammalian cells and how they have shaped the hypothesis that all cells are capable of circadian rhythmicity.